A Comparative Study in Ethical Awareness of Experienced and Novice Tax Practitioners in Guam - Suez-Sales , Martha G. (Journal of Accounting and Finance, 2021)
This study aims to assess differences in ethical awareness of experienced and novice tax compliance practitioners in Guam (U.S. Territory). Novices need to be prepared to recognize ethical content and have a thorough understanding of codes of conduct, rules, and standards of practice guided by the AICPA’s Statements on Standards for Tax Services (AICPA SSTS) and the Internal Revenue Service Circular 230 (Circular 230). This paper focuses on identifying gaps and vulnerabilities of young professionals associated with ethical sensitivity. First, this study proposes that when newcomers enter the workplace, they rely on a teleological ethical approach based on their own convictions to recognize ethical tax compliance issues. Through the process of socialization, these individuals begin to share organizational and professional values gradually adopting a deontological approach. Second, this study also finds that in the presence of conflicting values between the organization and tax ethical principles, experienced practitioners high on idealism strongly favored the latter. Third, challenges and deficiencies in ethical recognition were identified among novice participants.